A wearable cardioverter defibrillator with a low false alarm rate. (28th February 2022) - Poole, Jeanne E.; Gleva, Marye J.; Birgersdotter‐Green, Ulrika; Branch, Kelley R. H.; Doshi, Rahul N.; Salam, Tariq; Crawford, Thomas C.; Willcox, Mark E.; Sridhar, Arun M.; Mikdadi, Ghiath; Beinart, Sean C.; Cha, Yong‐Mei; et al.
Abstract: Introduction: A wearable cardioverter defibrillator (WCD) is indicated in appropriate patients to reduce the risk for sudden cardiac death. Challenges for patients wearing a WCD have been frequent false shock alarms primarily due to electrocardiogram noise and wear discomfort. The objective of this study was to test a contemporary WCD designed for reduced false shock alarms and improved comfort. Methods: One hundred and thirty patients with left ventricular ejection fraction ≤40% and an active implantable cardioverter defibrillator (ICD) were fitted with the ASSURE WCD (Kestra Medical Technologies) and followed for 30 days. WCD detection was enabled and shock alarm markers recorded, but shocks and shock alarms were disabled. All WCD episodes and ICD ventricular tachycardia/ventricular fibrillation (VT/VF) episodes were adjudicated. The primary endpoint was the false‐positive shock alarm rate with a performance goal of 1 every 3.4 days (0.29 per patient‐day). Results: Of 163 WCD episodes, 4 were VT/VF and 159 non‐VT/VF (121 rhythms with noise, 32 uncertain with noise, 6 atrial flutter without noise). Only three false‐positive shock alarm markers were recorded; one false‐positive shock alarm every 1333 patient‐days (0.00075 per patient‐day, 95% confidence interval: 0.00015–0.00361; p  < .001). No ICD recorded VT/VF episodes meeting WCD detection criteria (≥170 bpm for ≥20 s) were missed by the WCD during 3501 patient‐days of use. Median wear was 31.0 days (interquartile range [IQR] 2.0) and median daily use 23.0 h (IQR 1.7). Adverse events were mostly mild: skin irritation (19.4%) and musculoskeletal discomfort (8.5%). Conclusion: The ASSURE WCD demonstrated a low false‐positive shock alarm rate, low patient‐reported discomfort, and no serious adverse events.